Winds of change: The BRICS Club of Nations chipping away at Western dominance the dawn of the New South - Len Ishmael (South Centre, 2025)
This era of polycrises, a global health pandemic coupled with wars in Europe and the Middle East, against the backdrop of Great Power rivalry and climate related emergencies, has profoundly affected all countries, rich and poor alike. Disproportionately affected have been those of the Global South for whom the World Bank has cautioned a "decade of lost development". As rising geopolitical tensions fuel security concerns, the nature of economic ties between countries is changing. Several countries - spearheaded by BRICS members - have started to consider alternatives to the Western financial institutional architecture in a bid to safeguard their own interests. These measures risk fragmenting the existing global financial infrastructure and derailing benefits derived from decades of economic integration in the face of new barriers to cross border investment, commerce, and trade. Recent research shows that trade restrictions have more than tripled since 2019, financial sanctions have expanded and the geopolitical risk index has also spiked, following Russia's invasion of Ukraine. After decades of accepting the West's rules, there is a sense that the era of the Global South is dawning, and that Western interests are no longer de facto those of the rest of the world. It is in this milieu that the BRICS and their initiatives take on heightened economic and political significance.
Keywords: 300; BRICS; De-dollarization; Gulf States; New South; South-South Cooperation